The impact of extreme weather events on budget balances and implications for fiscal policy - Eliza M. Lis; Christiane Nickel (European Central Bank (ECB), 2009)
This paper explores implications of climate change for fiscal policy by assessing the impact of large scale extreme weather events on changes in public budgets. We apply alternative measures for large scale extreme weather events and conclude that the budgetary impact of such events ranges between 0.23% and 1.1% of GDP depending on the country group. Developing countries face a much larger effect on changes in budget balances following an extreme weather event than do advanced economies. Based on these findings, we discuss implications for fiscal policy and publiclyprovided disaster insurance. Our policy conclusions point to the enhanced need to reach and maintain sound fiscal positions given that climate change is expected to cause an increase in the frequency and severity of natural disasters.
Keywords: Q54; Q58; F59; H87; 330; climate change; disasters; Fiscal sustainability; Global warming; Klimawandel; Katastrophe; Öffentlicher Haushalt; Finanzpolitik; Nachhaltigkeit; Entwicklungsländer; EU-Staaten; OECD-Staaten; Welt